2013
DOI: 10.5539/ies.v6n4p93
|View full text |Cite
|
Sign up to set email alerts
|

The Level of E-Learning Integration at the University of Jordan: Challenges and Opportunities

Abstract: E-Learning is playing a significant role in education to improve students' skills and teach them new ways for managing their knowledge and information. Many universities and institutions of higher education have recognized the value of the Internet in changing the way people learn. Traditional classroom courses can be augmented with interactive materials on the Web and old fashioned courses can be transformed into e-Learning environments. However, few academic institutions have been able to embrace e-Learning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
27
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 23 publications
4
27
0
1
Order By: Relevance
“…As demonstrated in Table 6, instructors (20.27%) and students (25%) found that there is a lack of technical support to address issues that users may face. This result is consistent with findings of studies which pointed out that insufficient technical support is a key challenge to fostering e-learning (Al-Shboul, 2013;Sife et al, 2007;Ssekakubo et al, 2011). This means that preparation of professional staff should be a first step before launching a system.…”
Section: External Challengessupporting
confidence: 81%
See 1 more Smart Citation
“…As demonstrated in Table 6, instructors (20.27%) and students (25%) found that there is a lack of technical support to address issues that users may face. This result is consistent with findings of studies which pointed out that insufficient technical support is a key challenge to fostering e-learning (Al-Shboul, 2013;Sife et al, 2007;Ssekakubo et al, 2011). This means that preparation of professional staff should be a first step before launching a system.…”
Section: External Challengessupporting
confidence: 81%
“…As a consequence, users face difficulty with e-learning and this, in turn, may lead them to seek different reasons to avoid it. Earlier literature also highlighted this issue (Ali & Magalhaes, 2008;Al-Shboul, 2013). In our interviews, this was clear from all respondents that:…”
Section: External Challengesmentioning
confidence: 99%
“…Although wide-ranging research has been carried out on implementation issues pertinent to elearning design, development, management, delivery, evaluation and operations (AdewoleOdeshi, 2014;Al-Shboul, 2013) instructors is primary considerations in adoption e-learning, and they play a crucial role in specifying the effectivity, success or inefficacy of adoption elearning (Ali Alamin&Elgabar, 2014;McGill, Klobas, &Renzi, 2014). Nevertheless, very little empirical research has been conducted on instructor adoption e-learning from the perspectives of user intention (Al-Shboul, 2013;Almarabeh, 2014;Nisperos, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…1. Η έλλειψη τεχνικών γνώσεων και δεξιοτήτων των διδασκόντων, που αναφέρεται σε 25 έρευνες (Alemu, 2015;Almuqayteeb, 2009;Al-Shboul, 2013;Asiyai, 2014;Awidi, 2013;Brun & Hinostroza, 2014;Chaputula, 2012;Ejinkeonye & Usoroh, 2016;Kiasari, 2012;King, 2010;Kisanga & Ireson, 2015;Kouninef et al, 2013;Marwan & Sweeney, 2010;Momoh, 2010;Obiri-Yeboah et al, 2013;Okolocha & Nwadiani, 2015;Reilly, 2014;Rolfe et al, 2008;Ungar & Baruch, 2016;Vajargah et al, 2010;Zare-ee, 2011). Σε ένα μέρος από αυτές τις έρευνες, υπάρχει η τάση από τους ερωτώμενους να αιτιολογήσουν τη δηλωμένη έλλειψη με εξωγενείς παράγοντες, όπως είναι η έλλειψη ευκαιριών επιμόρφωσης/επαγγελματικής ανάπτυξης (Awidi, 2013;Marwan & Sweeney, 2010;Vajargah et al, 2010) ή το γεγονός ότι δεν έχουν λάβει αποτελεσματική κατάρτιση στη χρήση των ΤΠΕ (Alemu, 2015;Almuqayteeb, 2009;Kiasari, 2012) ή απλά ότι δεν διαθέτουν χρόνο για εκμάθηση (Reilly, 2014).…”
Section: ερευνητικό ερώτημα έρευνεςunclassified